1994
DOI: 10.1007/bf00193409
|View full text |Cite
|
Sign up to set email alerts
|

Factors causing different properties at neuromuscular junctions in fast and slow rat skeletal muscles

Abstract: Neuromuscular junctions on fast and slow skeletal muscle fibers have different properties. Possible reasons for these differences were examined in adult rat soleus (SOL) muscle fibers reinnervated at new ectopic or old denervated sites by fast fibular (FIB) or slow SOL motoneurons. FIB motoneurons formed large ectopic junctions with a high density of nerve terminal varicosities (fast appearance), whereas SOL motoneurons formed small ectopic junctions with a low density of varicosities (slow appearance). Both F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
1

Year Published

1999
1999
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 52 publications
2
30
1
Order By: Relevance
“…Thus, in the rat, synaptic area is greater in soleus slow fibers than in EDL fast fibers (839,874), but the ratio between NMJ area and fiber size is very similar in both muscles. The size of the vesicular pool is accordingly larger in soleus than in EDL.…”
Section: Transmission Of Nerve Impulse To Muscle Fibersmentioning
confidence: 85%
“…Thus, in the rat, synaptic area is greater in soleus slow fibers than in EDL fast fibers (839,874), but the ratio between NMJ area and fiber size is very similar in both muscles. The size of the vesicular pool is accordingly larger in soleus than in EDL.…”
Section: Transmission Of Nerve Impulse To Muscle Fibersmentioning
confidence: 85%
“…Limb muscles differ substantially in activation history, functional demands, and contraction patterns. 5,6,42 Thus, reported differences in function at the neuromuscular junction may reflect influences other than specific effects of motor units, including differences in muscle loading, activation history, and synaptic input. 26,27 In this regard, the study of a single muscle of mixed fiber-type composition may elucidate fiber type-specific differences in neuromuscular transmission.…”
Section: Discussionmentioning
confidence: 93%
“…Therefore, in the present study, the total numbers of both quiescent and mitotically active satellite cells, as well as the myonuclear number, were counted in whole fibers with central versus peripheral myonuclei. Waerhaug and Lomo [1994] reported that fast motoneurons form large ectopic junctions, whereas slow motoneurons form small ectopic junctions, concluding that the type of motoneuron, not muscle fiber, determines the fast or slow character of the neuromuscular junction (NMJ). Changes in the distribution of acetylcholine receptors were also observed in muscle fibers of mdx mice [Torres and Duchen, 1987;Lyons and Slater, 1991;Minatel et al, 2001;Personius and Sawyer, 2005].…”
Section: Introductionmentioning
confidence: 99%